(untitled) - Drummond, H. Evan (Upper Saddle River, N.J., 2004)
This provides knowledge about agricultural economics from a broad perspective that emphasizes the linkages between and among financial institutions, the macro economy, world markets, government programs, farms, agribusinesses, food marketing, farm services, and the environment.
Keywords: Agriculture,Nông nghiệp; Economic aspects,Khía cạnh kinh tế; United States,Hoa kỳ